(untitled) (Quinto Sol, 2013)
In this work, in favor of a historiographical renewal, we propose to reopen the debate around certain elements that problematize the contradictions of ranchers in their dynamics of articulation with other sectors of society and with the State, their difficulties to strengthen their organic insertion in the institutional structures and the centrality of the State as the supreme regulatory arbiter of the exercise of political domination.